The Economics of Corporate and Business Tax Reform - Dhammika Dharmapala (Center for Economic Studies and ifo Institute (CESifo), 2016)
The reform of corporate and business taxation is central to current tax policy debates in the United States. This paper provides a framework for analyzing reform proposals by describing the lessons from current economic research for business tax reform, addressing both international and domestic reforms within a unified perspective. The paper begins by identifying ten potential inefficiencies created by the current corporate tax regime. It then discusses three classes of reform proposals. The first involves a substantially lower corporate tax rate and a territorial regime. The second is a formula apportionment system. The third category includes a destination-based cash flow tax. The paper evaluates each of these proposals in the light of the framework introduced earlier. It concludes that the relatively modest reforms currently under discussion would address only a few of these margins. In contrast, more fundamental reforms would eliminate all or most of the inefficiencies of corporate taxation.
Keywords: H25; F23; 330; corporate tax; business taxation; international taxation; tax reform; territorial taxation; formula apportionment; cash flow tax